تأثیر فعالیة ادارة الوقت على التحصیل الدراسى لطلاب التدریب المیدانى فى أقسام المکتبات - د.عماد عبد الستار زیدان (المجلة الدولية لعلوم المكتبات والمعلومات)
The study examines the effect of the effectiveness of time managementfor the field training students in the library departments on academicachievement. The study imposed differences according to gender, place ofresidence and economic level in the ability to manage time for students. Acorrelation was also established between the ability to manage time and theability of students to attain field training.It aims to identify the reality of time management for field trainingstudents and its impact on academic achievement, identify behaviors thathelp field training students increase their awareness of the importance oftime, increase their ability to plan and organize time and identify behaviorsthat hinder field training students in managing their time.The most important results of the study is that there is no difference inthe ability to manage time according to gender and place of residence. Thestudy also highlighted that students with an average level of economics havemore time management ability than high-level students. The ability of currentfield training students to manage time does not help them increase theirlearning achievement